Identification and stress-induced expression of three 3β-hydroxysteroid dehydrogenases from Erysimum crepidifolium Rchb. and their putative role in cardenolide biosynthesis - Munkert, Jennifer; Ernst, Mona; Müller-Uri, Frieder; Kreis, Wolfgang (Phytochemistry, 2014)

Knockout of arabidopsis thaliana vep1, encoding a prise (Progesterone 5β-reductase/iridoid synthase-like enzyme), leads to metabolic changes in response to exogenous methyl vinyl ketone (mvk) - Klein, Jan; Ernst, Mona; Christmann, Alexander; Tropper, Marina; Leykauf, Tim; Kreis, Wolfgang; Munkert, Jennifer (Metabolites, 2022)
Small or specialized natural products (SNAPs) produced by plants vary greatly in structure and function, leading to selective advantages during evolution. With a limited number of genes available, a high promiscuity of the enzymes involved allows the generation of a broad range of SNAPs in complex metabolic networks. Comparative metabolic studies may help to understand why—or why not—certain SNAPs are produced in plants. Here, we used the wound-induced, vein patterning regulating VEP1 (AtStR1, At4g24220) and its paralogue gene on locus At5g58750 (AtStR2) from Arabidopsis to study this issue. The enzymes encoded by VEP1-like genes were clustered under the term PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes) as it was previously demonstrated that they are involved in cardenolide and/or iridoid biosynthesis in other plants. In order to further understand the general role of PRISEs and to detect additional more “accidental” roles we herein characterized A. thaliana steroid reductase 1 (AtStR1) and compared it to A. thaliana steroid reductase 2 (AtStR2). We used A. thaliana Col-0 wildtype plants as well as VEP1 knockout mutants and VEP1 knockout mutants overexpressing either AtStR1 or AtStR2 to investigate the effects on vein patterning and on the stress response after treatment with methyl vinyl ketone (MVK). Our results added evidence to the assumption that AtStR1 and AtStR2, as well as PRISEs in general, play specific roles in stress and defense situations and may be responsible for sudden metabolic shifts.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Arabidopsis thaliana; Reactive electrophile species; Specialized metabolism; Steroid reductase

Overexpression and RNAi-mediated Knockdown of Two 3β-hydroxy-Δ5-steroid dehydrogenase Genes in Digitalis lanata Shoot Cultures Reveal Their Role in Cardenolide Biosynthesis - Leykauf, Tim; Klein, Jan; Ernst, Mona; Dorfner, Maja; Ignatova, Anastasiia; Kreis, Wolfgang; Lanig, Harald; Munkert, Jennifer (Planta Medica, 2023)
3β-hydroxy-Δ5-steroid dehydrogenases (3βHSDs) are supposed to be involved in 5β-cardenolide biosynthesis. Here, a novel 3βHSD (Dl3βHSD2) was isolated from Digitalis lanata shoot cultures and expressed in E. coli. Recombinant Dl3βHSD1 and Dl3βHSD2 shared 70% amino acid identity, reduced various 3-oxopregnanes and oxidised 3-hydroxypregnanes, but only rDl3βHSD2 converted small ketones and secondary alcohols efficiently. To explain these differences in substrate specificity, we established homology models using borneol dehydrogenase of Salvia rosmarinus (6zyz) as the template. Hydrophobicity and amino acid residues in the binding pocket may explain the difference in enzyme activities and substrate preferences. Compared to Dl3βHSD1, Dl3βHSD2 is weakly expressed in D. lanata shoots. High constitutive expression of Dl3βHSDs was realised by Agrobacterium-mediated transfer of Dl3βHSD genes fused to the CaMV-35S promotor into the genome of D. lanata wild type shoot cultures. Transformed shoots (35S:Dl3βHSD1 and 35S:Dl3βHSD2) accumulated less cardenolides than controls. The levels of reduced glutathione (GSH), which is known to inhibit cardenolide formation, were higher in the 35S:Dl3βHSD1 lines than in the controls. In the 35S:Dl3βHSD1 lines cardenolide levels were restored after adding of the substrate pregnane-3,20-dione in combination with buthionine-sulfoximine (BSO), an inhibitor of GSH formation. RNAi-mediated knockdown of the Dl3βHSD1 yielded several shoot culture lines with strongly reduced cardenolide levels. In these lines, cardenolide biosynthesis was fully restored after addition of the downstream precursor pregnan-3β-ol-20-one, whereas upstream precursors such as progesterone had no effect, indicating that no shunt pathway could overcome the Dl3βHSD1 knockdown. These results can be taken as the first direct proof that Dl3βHSD1 is indeed involved in 5β-cardenolide biosynthesis.<br

RNAi-mediated gene knockdown of progesterone 5β-reductases in Digitalis lanata reduces 5β-cardenolide content - Klein, Jan; Horn, Elisa; Ernst, Mona; Leykauf, Tim; Leupold, Tamara; Dorfner, Maja; Wolf, Laura-Sophie; Ignatova, Anastasiia; Kreis, Wolfgang; Munkert, Jennifer (Plant Cell Reports, 2021)
Key message: Studying RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of Digitalis lanata, we here provide direct evidence for the participation of PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes) in 5β-cardenolide formation. Abstract: Progesterone 5β-reductases (P5βR) are assumed to catalyze the reduction of progesterone to 5β-pregnane-3,20-dione, which is a crucial step in the biosynthesis of the 5β-cardenolides. P5βRs are encoded by VEP1-like genes occurring ubiquitously in embryophytes. P5βRs are substrate-promiscuous enone-1,4-reductases recently termed PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes). Two PRISE genes, termed DlP5βR1 (AY585867.1) and DlP5βR2 (HM210089.1) were isolated from Digitalis lanata. To give experimental evidence for the participation of PRISEs in 5β-cardenolide formation, we here established several RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of D. lanata. Cardenolide contents were lower in D. lanata P5βR-RNAi lines than in wild-type shoots. We considered that the gene knockdowns may have had pleiotropic effects such as an increase in glutathione (GSH) which is known to inhibit cardenolide formation. GSH levels and expression of glutathione reductase (GR) were measured. Both were higher in the Dl P5βR-RNAi lines than in the wild-type shoots. Cardenolide biosynthesis was restored by buthionine sulfoximine (BSO) treatment in Dl P5βR2-RNAi lines but not in Dl P5βR1-RNAi lines. Since progesterone is a precursor of cardenolides but can also act as a reactive electrophile species (RES), we here discriminated between these by comparing the effects of progesterone and methyl vinyl ketone, a small RES but not a precursor of cardenolides. To the best of our knowledge, we here demonstrated for the first time that P5βR1 is involved in cardenolide formation. We also provide further evidence that PRISEs are also important for plants dealing with stress by detoxifying reactive electrophile species (RES).
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cardenolide biosynthesis; Digitalis lanata; Glutathione; Progesterone 5β-reductases (P5βR); Reactive electrophile species; RNAi-mediated knockdown

Steroid 5β-reductase from leaves of Vitis vinifera: molecular cloning, expression and modelling - Ernst, Mona; Munkert, Jennifer; Campa, Manuela; Malnoy, Mickael; Martens, Stefan; Müller-Uri, Frieder (Journal of Agricultural and Food Chemistry, 2015)